Cara Pengawetan Ikan Mas (Cyprinus carpio L) Dengan Menggunakan Fermentasi Limbah Kubis (Brassica oleracea) - Misril Fuadi; Surnaherman , (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
The research on the utilization of waste cabbage (Brassica oleracea) as a preservative tilapia (Oreochromis sp) with RAL factorial method with 2 replications.The first factor is the concentration of NaCl with a password (N) which consists of 4 levels, namely: N1 = 1%, N2 = 2%, N3 = 3% , N4 = 4%. Factor II is a password storage time (P) which consists of 4 levels, namely: P1 = 1 days, P2 =3 days, P3 = 5 days, P4 = 7 days.The parameters observed from the data analysis showed that NaCl concentration and storage time significantly affected the protein content, moisture content, organoleptic aroma, texture organoleptic tests,and organoleptic color not significant. Keywords: longdepository,concentration sodium chloride